Revival of local masking traditions in Latvia as the result of cooperation between performers and researchers - Rancane, Aida (Traditiones (Ljubljana), 2012)
At a time when it is possible to identify oneself with the global and universal, an opposite process is also occurring: an increase in interest in the local. This article describes the process of renewing three previously interrupted traditions. Is it possible to reconstruct a tradition at all, and what are the general conditions of cooperation between the researchers and participants to ensure a successful process?
Keywords: ethnology; Etnologija; globalizationa; Način življenja; folk culture; Ljudska kultura; Kulturna dediščina; cultural heritage; Globalizacija; globalization; ljudski običaji; pust; maske; maskiranje; Latvija